2003
DOI: 10.1038/sj.ijo.0802386
|View full text |Cite
|
Sign up to set email alerts
|

Long-term body weight variability is associated with elevated C-reactive protein independent of current body mass index among Japanese men

Abstract: OBJECTIVE:To elucidate the effect of long-term weight variability on C-reactive protein (CRP) levels. DESIGN: Cross-sectional study of the circulating CRP. SUBJECTS: A total of 637 Japanese men aged 40-49 y in1997. MEASUREMENTS: Serum CRP levels, body mass index in 1997 (current BMI), the slope of weight on age (weight-slope) representing an individual's weight trend of direction and magnitude, and the root mean square error around the slope of weight on age (weight-RMSE) representing the weight fluctuation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 25 publications
3
29
0
2
Order By: Relevance
“…Two studies in humans found a positive association of weight fluctuation with waist -hip ratio 22 or truncal adiposity. 18 Interestingly, when our data were dichotomized at BMI 25 kg/m 2 , the association between weight fluctuation and MS or each component of MS was pronounced only among subjects with BMI <25 kg/m 2 , which is consistent with other studies 9,14,23 in which adverse effects of weight change on health were seen more often among those who were not overweight, than among those who were overweight. The weight -RMSE value may reflect the degree of total or abdominal adiposity more exactly among normal-weight subjects than among obese ones.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Two studies in humans found a positive association of weight fluctuation with waist -hip ratio 22 or truncal adiposity. 18 Interestingly, when our data were dichotomized at BMI 25 kg/m 2 , the association between weight fluctuation and MS or each component of MS was pronounced only among subjects with BMI <25 kg/m 2 , which is consistent with other studies 9,14,23 in which adverse effects of weight change on health were seen more often among those who were not overweight, than among those who were overweight. The weight -RMSE value may reflect the degree of total or abdominal adiposity more exactly among normal-weight subjects than among obese ones.…”
Section: Discussionsupporting
confidence: 79%
“…BMI was calculated as weight in kilograms divided by the square of height in meters and used as an index for obesity. Similar to our previous study, 14 weight variability was divided into 2 distinct components, that is, trend over time and fluctuation over time, using a simple linear regression model in which each value of the subject's actual weights at ages 20, 25, 30 years, 5 years ago, and present age were the 5 dependent variables and the subject's age at each examination the independent variables. The slope coefficient of this model was used as an index representing the trend of an individual's weight changes in terms of direction and magnitude (weight -slope), and the root mean square error (RMSE) of this model, a standard deviation around this slope, was used to represent the magnitude of weight fluctuation (weight -RMSE).…”
Section: Body Size and Weight Variability Indicesmentioning
confidence: 99%
“…However, as previously reported [21,33,61,66], we found that increased levels of BMI were strongly associated with increases in CRP levels (r = 0.831, β = 3.714, P = 0.000). Furthermore, elevated levels of other inflammatory markers including interleukin 1 and 6 (IL-1, 6), tumour necrosis factor α and β (TNFα, β) have been reported in obese individuals [4,11,74].…”
Section: Discussionsupporting
confidence: 63%
“…The association between excess adipose tissue (measured either indirectly by body mass index [BMI] or directly by body composition assessment) and elevated CRP concentrations [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] has been observed to hold for children, 36,40,45 elderly…”
Section: Role Of Adiposity and Weight Loss In Regulating Inflammationmentioning
confidence: 99%